Comparing the effectiveness of the unified protocol in combination with an additional mindfulness treatment to the unified protocol alone as treatment for adolescents diagnosed with emotional disorders - Maleki,Mahboobeh (2021)
Abstract Objective Many adolescents suffer from depressive and anxiety disorders simultaneously and current treatment methods do not put enough emphasis on comorbidity of these disorders. The unified protocol for treating emotional disorders in adolescents is a transdiagnostic therapy which targets mutual fundamental factors. Therefore, the current study aims to compare the effectiveness of the unified protocol alone with the unified protocol combined with mindfulness as an additional treatment in adolescents suffering from emotional disorders. Method A quasi-experimental study was conducted with adolescents. The participants had been diagnosed with emotional disorders and were divided into a control group (15 participants) and an experimental group (16 participants). Both groups were offered 14 sessions of therapy. They were assessed at pre-test, post-test, and two-month follow-up. Scales used in the study included the Child Behavior Checklist (CBCL), the Children’s Depression Inventory (CDI), and the Youth Anxiety Measure for DSM-5 (YAM-5). Results The results showed that both of the treatment methods effectively reduced adolescents’ emotional problems, but improvements were more significant in the group administered the additional mindfulness program. Among the variables assessed, non-phobic anxiety disorders and depression improved more than specific phobia and behavioral problems. Between-subjects (Group) partial etas for non-phobic anxiety, depression, specific phobia, and behavioral problems were 0.67, 0.50, 0.23, and 0.16, respectively. Conclusion According to the findings of this study, additional treatment methods such as mindfulness could increase the effectiveness of the unified transdiagnostic protocol for adolescents (UP-A). The therapeutic implications are discussed.